DISCURSO, VIOLÊNCIA E ESPETACULARIZAÇÃO DA NOTÍCIA: EFEITOS DE SENTIDO EM TORNO DA MADRASTA. - Tafuri, Leandro (2014)
This study, entitled "Speech, violence and spectacularization of the news: effects of meaning around the stepmother" is based on Discourse Analysis of French foundation and Brazilian continuity, theoretical and analytical movement in which we tie the notions of spectacle coming from media.Thus, this research constitutes a relationship of language / Journalism interface, in which we take as the object of study the discourse on violence in urban setting. The main objective is to analyze the discourses about death as a spectacle, from stories that bring the main focus, news about crimes, that have shocked and aroused the society interest, the news were spectacularized by media and have entered the center of discussions.To do so, we cut out the crimes depicted in the media as events, searching for discursivization and the ways these discourses break up with the normality by " identifier norm". Considering these discourses in a given socio-historical moment and in a particular conditions of production, we aim to understand which regularities and ruptures pervade the discourse about death as a spectacle in contemporary urban space and how the criminals subjects are signified / represented in the journalistic text. It is noteworthy that, from the place where we look at our object, the journalistic text is designed as a symbolic practice, that works in the discourse as significant materiality, because from it resonate different effects meaning . To understand the regularities and disruptions that pervade the discourse about death, we will map out the regularities and ruptures, as processes in action, surrounding the death as a spectacle on weekly magazine covers of large circulation, searching for effects of senses from the discourses that sustain them, while memory - speech of. Among the speeches about death as spectacle, we took as corpus what was discoursed around of Isabela Nardoni`s murder, from the representation of the female subject by the designation of the stepmother, as well as memories and speeches that return by her / in her.